Post-stroke seizures in animal models: a systematic review and meta-analysis - Csernyanszki, Kayla D. L.; Nyenke-Wofuru, Nmazule K.; Olsen, McKenzee M.; Grenier, Amelie V.; Hwata, Hazel; Klahr, Ana C. (Frontiers in Neuroscience, 2025)
BackgroundPost-stroke seizures (PSS) are a common complication of stroke and can exacerbate neurological injury, yet their study in preclinical models remains limited. Understanding the relationship between PSS and outcomes in animal models is critical for improving translational research and informing therapeutic strategies.ObjectiveTo systematically review and meta-analyze the incidence, consequences, and methodological quality of studies investigating PSS in animal models of ischemic stroke (IS) and intracerebral hemorrhage (ICH).MethodsA systematic search of Embase, Medline, Scopus, and Web of Science (June 2024, updated May 2025) identified original, peer-reviewed animal studies published after 1999 that reported seizures and outcomes (lesion volume, neurological deficit scores, behavior, edema, inflammation) without interventional treatments. Data extraction, risk-of-bias assessment, and a random-effects meta-analysis was performed for lesion volume.ResultsOf 6,005 studies screened, 10 met inclusion criteria, with eight eligible for meta-analysis. Seizure incidence ranged from 17.5–82% in focal ischemia and 45–67% in ICH models. Lesion volume was the most commonly measured outcome. Meta-analysis revealed that seizures were associated with larger lesion volumes in focal ischemia models (Hedge’s G = 1.598, p = 0.038) but not in ICH models (Hedge’s G = 0.180, p = 0.468). Across studies, seizures were linked to more severe neurological deficits in focal ischemia but showed no consistent effect in ICH. Risk-of-bias assessment indicated high risk in all studies, with frequent methodological limitations including lack of random outcome assessment, use of only young male animals, and absence of a priori sample size calculations. Publication bias was suggested by funnel plot asymmetry.ConclusionThis review highlights a scarcity of rigorous preclinical studies on PSS, substantial heterogeneity across animal models, and methodological limitations that hinder translatability. Findings suggest a differential impact of stroke type on seizure outcomes, with focal ischemia-associated seizures linked to larger lesions and poorer neurological function. Future research should employ long-term, rigorously designed studies using diverse animal populations, standardized seizure monitoring, and careful reporting to enhance clinical relevance and guide therapeutic development.